Draft Annual Plan 2006-2007 Maharashtra State Part I - Planning Commission (Planning Commission, 2006)
The priorities as determined by the National Development Council (NDC) in September 2001 for the Tenth Five Year Plan have reflected in the earlier two annual plans of the State. These priorities shall continue to have sufficient outlay in the Annual Plan 2006. Priorities of the Annual Plan 2006-2007 The priorities, as determined by the National Development Council (NDC) in September 2001 are as under Accelerated economic development through infrastructural development (with more private initiative in all possible sectors) ensuring high speed industrial development and creating employment on large scale. Growth rate of 8% in GDP.
Planning Department Government of Maharashtra